Evaluation of Cutting Forces and Temperature of Iron-Rich Binder Carbide Tool in Turning of Titanium - MAHADEVAIAH, Chandrashekar; PRASAD, Sreenivasa (Engineering Transactions, 2018)
The machining of titanium has been understood to be challenging and costly due to its material properties such as low thermal conductivity, low modulus of elasticity, high strength at elevated temperatures and chemical reactivity. This work aims to study the effect of iron as a partial substitution along with cobalt binder as the tool material for machining of titanium alloy. In this work, iron-rich binder tool (WC-Co-Fe) and cobalt binder tool (WC-Co) samples were produced by powder metallurgy route using powders with a mean particle size of less than 0.5 μm. Next, the evaluation of mechanical properties and phase analysis were performed. Turning experiments were conducted at various cutting speeds, feed and depth of cut (DOC), to evaluate the effects of iron-rich binder on flank wear, cutting forces and cutting temperature.The obtained results of turning experiments reveal that iron-rich binder tends to increase cutting performance in comparison to conventional WC-Co composite cutting tools.